How does varying water supply affect oxygen isotope variations in needles and tree rings of Scots pine?. (26th June 2020) - Timofeeva, Galina; Treydte, Kerstin; Bugmann, Harald; Salmon, Yann; Rigling, Andreas; Schaub, Marcus; Vollenweider, Pierre; Siegwolf, Rolf; Saurer, Matthias
Abstract: In many regions, drought is suspected to be a cause of Scots pine decline and mortality, but the underlying physiological mechanisms remain unclear. Because of their relationship to ecohydrological processes, δ 18 O values in tree rings are potentially useful for deciphering long-term physiological responses and tree adaptation to increasing drought. We therefore analyzed both needle- and stem-level isotope fractionations in mature trees exposed to varying water supply. In a first experiment, we investigated seasonal δ 18 O variations in soil and needle water of Scots pine in a dry inner Alpine valley in Switzerland, comparing drought-stressed trees with trees that were irrigated for more than 10 years. In a second experiment, we analyzed twentieth-century δ 18 O variations in tree rings of the same forest, including a group of trees that had recently died. We observed less 18 O enrichment in needle water of drought-stressed compared with irrigated trees. We applied different isotope fractionation models to explain these results, including the Péclet and the two-pool correction, which considers the ratio of unenriched xylem water in the needles to total needle water. Based on anatomical measurements, we found this ratio to be unchanged in drought-stressed needles, although they were shorter. The observed lower 18 O enrichment in needles of stressed trees was therefore likely caused by increased effective path length for water movement within the leaf lamina. In the tree-ring study, we observed lower δ 18 O values in tree rings of dead trees compared with survivors during several decades prior to their death. These lower values in declining trees are consistent with the lower needle water 18 O enrichment observed for drought-stressed compared with irrigated trees, suggesting that this needle-level signal is reflected in the tree rings, although changes in rooting depth could also play a role. Our study demonstrates that long-term effects of drought are reflected in the tree-ring δ 18 O values, which helps to provide a better understanding of past tree physiological changes of Scots pine.